2021
DOI: 10.1080/20961790.2021.1970887
|View full text |Cite
|
Sign up to set email alerts
|

The Next Steps in Academic Integrity — Education, Awareness, Norms, Duty and Law

Abstract: We conducted and analyzed several internet surveys in order to understand the profile of global research integrity and ethical awareness, encompassing global population distribution. These were (1) the global distribution of Committee of Publishing Ethics (COPE) membership; (2) the global distribution of "Integrity" or "Ethics" journals;(3) the level of academic integrity awareness in European higher education institutions and (4) awareness of academic integrity in the top universities of Asia and Africa. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Furthermore, their findings indicated that students who are aware of academic integrity had a positive impact by sharing their knowledge with their peers (Khan et al, 2020). As a result, education and awareness are especially important in promoting academic integrity (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their findings indicated that students who are aware of academic integrity had a positive impact by sharing their knowledge with their peers (Khan et al, 2020). As a result, education and awareness are especially important in promoting academic integrity (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the efficacy of the multitude of interventions and training programs in academic integrity, Sefcik et al (2019) note a lack of focus on values and consequences of misconduct. Zhang et al (2021) see the greatest issue as a lack of awareness and suggest the use of an academic integrity awareness index. This body of research suggests focussing on the ethical values underlying codes of conduct may be helpful in an educational context.…”
Section: Security Awareness and Practice Of University Studentsmentioning
confidence: 99%
“…(2019) note a lack of focus on values and consequences of misconduct. Zhang et al. (2021) see the greatest issue as a lack of awareness and suggest the use of an academic integrity awareness index.…”
Section: Background Literature and Research Questionsmentioning
confidence: 99%
“…Our statement is confirmed in research of 2021 of scientists Yuehong (Helen) Zhang, Hanfeng Lin, Xinxin Zhang, Qing Ye that based on a survey of academic integrity on six continents and population data. The scientists concluded that the global awareness of academic integrity and publishing ethics around the world is imbalanced, especially in the developing countries where population density is at it's highest (Zhang et al, 2021).…”
Section: Academic Integrity In the World As An Indicator Of The Quali...mentioning
confidence: 99%